Analysis of Soil Characteristics by Layer Based on the Robertson Et Al and Schmertmann Method from CPT (Cone Penetration Test) - Siti Nur Indah Sari; Dwi Wahyuni (Program Pascasarjana Universitas Sriwijaya, 2023)
Soil is the sub-base where the building structure is located, and the soil classification differs for each layer. There are many cases of failure in building construction due to poor soil, causing the building structure to crack and even collapse, which causes damage to the building - material and also dangerous for the building occupants. For this reason, soil investigation is significant to conduct before constructing the upper structure. One of them is the Sondir test. However, when the sondir data analysis of the qc and FR values are obtained, the Robertson et al method and the Schmertmann method will show the result of soil layer classification before construction begins. The research was located in a specific area, Bengkalis Road, Belawan Medan City, and North Sumatra. The research suggests that the soil in this location is predominantly soft with low shear resistance (qc ranging from 0 - 5 kg/m2), clay type, and depths of 6 - 7 meters. Due to these soil conditions, there are certain considerations and precautions that need to be taken into account if you plan to build on this land. One of them, soil improvement is given the soft and low shear resistance characteristics of the soil, its techniques may be necessary before construction. The suggested depth for the pile foundation is 10 - 20 meters. The actual depth would depend on factors such as the specific characteristics of the soil layers and the weight of the planned structure.